Pengaruh Penggunaan Aplikasi “Bumil Bahagia” Berbasis Android terhadap Tingkat Pengetahuan Faktor Risiko PEAD pada Ibu Hamil di Kabupaten Banyumas - Mulhamatus Latifatus Suri; Wilis Dwi Pangesti (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2024)
Preeclampsia is one of the biggest problems in pregnancy and is a cause of infant and maternal death every year in the world. The low knowledge of pregnant women is one of the factors in recognizing the condition of their pregnancy. The use of digital health brings a lot of medical information exchange between patients and health workers, health services in the context of differential diagnosis, access to health is more efficient and cost effective. This study aims to determine the effect of using the android-based